Modelling human liver microphysiology on a chip through a finite element based design approach. (16th February 2021) - Menezes, Pedro Duarte; Gadegaard, Nikolaj; Natal Jorge, Renato M.; Pinto, Sónia I. S.
Abstract: Organ‐on‐a‐chip (OoaC) are microfluidic devices capable of growing living tissue and replicate the intricate microenvironments of human organs in vitro, being heralded as having the potential to revolutionize biological research and healthcare by providing unprecedented control over fluid flow, relevant tissue to volume ratio, compatibility with high‐resolution content screening and a reduced footprint. Finite element modelling is proven to be an efficient approach to simulate the microenvironments of OoaC devices, and may be used to study the existing correlations between geometry and hydrodynamics, towards developing devices of greater accuracy. The present work aims to refine a steady‐state gradient generator for the development of a more relevant human liver model. For this purpose, the finite element method was used to simulate the device and predict which design settings, expressed by individual parameters, would better replicate in vitro the oxygen gradients found in vivo within the human liver acinus. To verify the model's predictive capabilities, two distinct examples were replicated from literature. Finite element analysis enabled obtaining an ideal solution, designated as liver gradient‐on‐a‐chip, characterised by a novel way to control gradient generation, from which it was possible to determine concentration values ranging between 3% and 12%, thus providing a precise correlation with in vivo oxygen zonation, comprised between 3%–5% and 10%–12% within respectively the perivenous and periportal zones of the human liver acinus. Shear stress was also determined to average the value of 0.037 Pa, and therefore meet the interval determined from literature to enhance liver tissue culture, comprised between 0.01 − 0.05 Pa . Abstract : The present paper focuses on developing a human liver model to accurately replicate oxygen zonation on a chip. A finite element approach was employed to manipulate the device's fluidic regime by refining its respective design features, aiming to generate enhanced gradients of oxygen characterising a microenvironment of greater physiological relevance. The established procedure ultimately enabled the obtention of a more relevant human liver model, for organ‐on‐a‐chip (OoaC) purposes, by precisely replicating oxygen zonation as found in vivo within the human liver acinus.